The American College of Surgeons as an advocate for global surgery awareness. Issue 1 (February 2022) - Bell, N.; Tefera, G.; Melone, M.; Bass, B.
Abstract: The American College of Surgeons (ACS), founded in 1913, is the one of the oldest surgical professional organizations in the United States. Originally founded to foster surgical professional excellence and collaboration among surgeons in North America, the ACS has now expanded to over 80, 000 members worldwide with programs delivering a rich portfolio of professional services in the domains of surgical education, clinical surgery and global surgery, surgical quality and leadership, surgical research, member services. ACS international programs initially focused on international professional exchange and hosting of young surgeons from around the world in US based surgical centers to develop scholarly and clinical collaborations. Over the last 20 years, with the founding of the ACS-Operation Giving Back (OGB) Program, the ACS has broadened its international perspective to support surgical care in emerging nations and to develop collaborative programs with host institutions in emerging nations to support surgical care capacity growth through on site partnerships, and educational and policy initiatives. To that end, in recent years, OGB has developed global surgical programs in the COSECSA region of sub-Saharan Africa creating opportunities to participate in Global Surgical Training Hubs. After developing a pilot hub project in Hawassa, Ethiopia, OGB is now in the process of scaling up two additional sites. In this manuscript, we will describe ACS's rich history of activities promoting international surgical collaboration and scholarship and discuss the process of creating the global surgical training hub model in Hawassa.